Effectiveness of point‐of‐use/point‐of‐entry systems to remove per‐ and polyfluoroalkyl substances from drinking water. Issue 2 (18th March 2019) - Patterson, Craig; Burkhardt, Jonathan; Schupp, Donald; Krishnan, E. Radha; Dyment, Stephen; Merritt, Steven; Zintek, Lawrence; Kleinmaier, Danielle
Abstract : The contamination of groundwater sources with per‐ and polyfluoroalkyl substances (PFAS) in the United States is a widespread problem for the drinking water industry. Well water supplies in the municipalities of Fountain, Security, and Widefield, Colorado, contain perfluorooctanoic acid and perfluorooctane sulfonate levels greater than the U.S. Environmental Protection Agency (USEPA) health advisory level of 70 ng/L. The source of PFAS has been associated with aqueous film‐forming foam at Peterson Air Force Base. To assist property owners and limit the exposure of PFAS to residential drinking water systems, treatability studies were conducted by the USEPA on the PFAS removal effectiveness of commercially available point‐of‐use/point‐of‐entry units using reverse osmosis treatment and granular activated carbon adsorbents. Household water systems were tested with a test water containing the water quality characteristics and six PFAS contaminants found in Widefield aquifer region groundwater samples. This study also documents the installation, startup, and continuous/intermittent operation of the treatment systems.